CHILDREN'S LITERATURE IN THE PROCESS OF LITERACY: CONSTRUCTION OF THE STATE OF KNOWLEDGE. - Ariana da Silva Fagundes Generoso; Maria ia Inês Côrte Vitór (Editora da Universidade de Santa Cruz do Sul, 2013)
This article aims to obtain a scenario of studies on the presence of children's literature in the classroom literacy of elementary school, from the Law No. 11,274, that foresee for the period of nine years for this stage of education. Therefore, we analyzed theses / dissertations from 2006 to 2011 on the theme broad and organized categories of the search. The portals ANPEd and CAPES were maintainers of corpus research. Six articles are suited to specific criteria arising from the portal of CAPES and one article from the portal ANPEd, among many who were surveyed, but who have not established relations with the requirements. The data obtained reflect a need for a more comprehensive research in the area of educating readers of literature in early stage of schooling.